Modelo Genérico Para La Creación De Microempresas Agroecológicas Basadas En El Conocimiento Y La Innovación Tecnológica En La Zona Rural De La Parroquia Febres Cordero Del Cantón Babahoyo. - Oviedo Campozano, Fulton David (2015)
According to author Miguel A. Altieri, in its so called text: “Agroecología. Scientific bases for an agriculture sustentable”, the agroecología delivers the rules for a careful handling of the agroecosistemas without provoking unnecessary or irreparable damage. Simultaneously with the effort to fight to the plagues, illnesses or shortcomings of the soil, The agroecólogo fights to return to the agroecosistema its elasticity and force. If the cause of the illnesses, plagues, soil degradation, etc. it assumes to an imbalance, then the goal of the treatment agroecológico will be of recovering the balance. In agroecología, the biodiversification is the main skill to restore the auto-regulation and to the sustentabilidad. Nevertheless, the ecological health is not the only goal of the agroecología. In fact, the sustentabilidad is not possible without preserving the cultural diversity that it nourishes to the local agricultures. A stable production can only be carried out inside the context of a social organization that protects the integrity of the natural resources and that assures the harmonic interaction of the human beings, the agroecosistema and the environment. (Altieri, Preface, 1999). It is established like alternative: “Microcompany model agroecológica for the production of not traditional products of the Parish Febres Cordero”, it becomes necessary to depart from the fact of which the agricultural production in this sector of the canton Babahoyo, is not properly tecnificada and from which the producers of the area realize its sembríos based on the traditional knowledge, in one cases inherited from its ancestor, in others for the experience in the consecutive sembríos who execute every production period of similar form or submitting to the modifications of the climate or the previous existing climatic conditions or during the sowing, experiences that we can indicate appear largely to the form of the harvest of traditional, such products like the rice, the soybean, the banana tree, the coffee, between others, therefore of the realized study one detaches that, as for not traditional cultivation, the producer of the area has little experience and knowledge on the processes that need the sembrío, especially the related one to the ecological thing and its aspects that derive in fortitude in its relation with the agricultural thing, this one is based in: (1) to Investigate the economic profitability of this type of developments and its related exogenous factors and (2) to Design a microcompany model agroecológica for the production of not traditional products of the Parish Febres Cordero.